PERAN AKAD RAHN DALAM PEMBIAYAAN UMKM: TINJAUAN LITERATUR FIQH MUAMALAH - Abdurrahman Putera Nugroho; Gama Gama; Muhammad Fattir Aufa Azzir; Muhammad Dzaki Al Faruq (Taksasila Edukasi Insani, 2025)
This study is about the role of rahn contracts in financing micro, small, and medium enterprises (MSMEs), which aims to increase the effectiveness of the use of rahn contracts in supporting access to sharia financing. The method used in this study is a descriptive qualitative approach through a study of relevant literature. The results of the study indicate that rahn contracts play a very important role in opening access to micro financing for MSME actors, especially through Islamic financial institutions such as Islamic pawnshops and Baitul Maal Wat Tamwil (BMT). In recent years, the use of rahn contracts has increased significantly because it is considered capable of providing fast, flexible financing solutions that are in accordance with the principles of justice and sharia. Rahn is an inclusive alternative for MSMEs that do not have fixed collateral and have difficulty accessing conventional financing.Keywords : Fiqh Muamalah, Islamic Finance, Microfinance, MSMEs, Rahn Contract